2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4440007
|View full text |Cite
|
Sign up to set email alerts
|

Coupled-bunch instability study of multi-cell deflecting mode cavities for the Advanced Photon Source

Abstract: The short-pulse X-ray project at the Advanced Photon Source (APS) uses four room-temperature, three-cell, 2.815-GHz, deflecting-mode cavities in two consecutive straight sections. Undamped, these cavities' higher-order and lower-order resonator modes will cause multi-bunch instabilities in longitudinal and transverse planes for any bunch pattern of a 100-mA store. Damping of these modes must be part of the design of the cavities. We report calculations of instability growth rates that were essential in specify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Beam dynamics in APS sets strict requirements on damping of of low-order-modes (LOM) and high-ordermodes (HOM) in the cavity [10]. We found that the best way to address these requirements was to use a pair of cavities instead of one long cavity.…”
Section: Deflecting Cavity Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Beam dynamics in APS sets strict requirements on damping of of low-order-modes (LOM) and high-ordermodes (HOM) in the cavity [10]. We found that the best way to address these requirements was to use a pair of cavities instead of one long cavity.…”
Section: Deflecting Cavity Designmentioning
confidence: 99%
“…The operating frequency of the deflector is the 8th harmonic of the APS ring RF frequency [10]. For this design we chose power and repetition rate similar to that of a commercially available klystron [12].…”
Section: Design Considerationsmentioning
confidence: 99%
“…With the h=8 as the chosen frequency, an in-depth study based on Monte-Carlo simulation has been performed, and the results are reported in Ref. [4]. …”
Section: Hybrid-fill Patternmentioning
confidence: 99%
“…Progress made in the various aspects of the project are reported in these proceedings, which include the overall configuration of a pulsed crab-cavity system and its implementation in the APS storage ring [2], rf design of crab-cavity system [3], and multi-bunch instability analysis for the APS storage ring with crabcavity installed [4]. Here we describe the single-bunch instability caused by a crab-cavity system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation